Odpowiedzi

  • Użytkownik Zadane
2009-09-26T11:01:12+02:00
A)√32 + √18 + √50 - √162 =
(√16×√2)+(√9×√2)+(√25×√2)-(√81×√2)=
4√2+3√2+5√2-9√2=3√2

b)4∛54 + 8∛128 - ∛250 =
(4×∛27×∛2)+(8×∛64×∛2)-(∛125×∛2)=
(4×3∛2)+(8×4∛2)-5∛2=12∛2+32∛2-5∛2=39∛2

c)√6¼ + √1 i 7/9 - √1/9 - 2√2¼=
(√²⁵/₄)+(√¹⁶/₉)-(√¹/₉)-(2×√⁹/₄)=
(⁵/₂)+(⁴/₃)-(¹/₃)-(2׳/₂)=
(¹⁵/₆)+(⁸/₆)-(²/₆)-3=
(²¹/₆)-3=3½-3=½
49 2 49
2009-09-26T11:19:10+02:00
A) √16*2 + √9*2 + √25*2 - √81*2 = 4√2+3√2+5√2-9√2 = 12√2 - 9√2 = 3√2
b) 4∛54 + 8∛128 - ∛250 = 4∛27*2 + 8∛64*2 - ∛125*2 = 4*3∛2 + 8*4∛2 - 5∛2 = 12∛2 + 32∛2 - 5∛3 = 39∛2
c) √6¼ + √1 i 7/9 - √1/9 - 2√2¼ = √25/4 + √16/9 - √1/9 - 2√9/4 =
5/2 + 4/3 - 1/3 - 2*(3/2) = 5/2 + 1 - 6/2 = 7/2 - 6/2 = 1/2
24 3 24